A multi‐scale characterisation of the durum wheat pasta cooking process. (13th December 2018) - Littardi, P.; Diantom, A.; Carini, E.; Curti, E.; Boukid, F.; Vodovotz, Y.; Vittadini, E.
Summary: A multi‐level investigation was carried out to characterise uncooked to overcooked pasta. Macroscopic, mesoscopic and molecular properties were measured and their changes were clearly related to the process of cooking: hardness and viscoelastic decreased, moisture content and gelatinisation degree increased and 1 H molecular mobility changed. Principal component analysis (PCA) explained 82% (PC1: 47.7% and PC2: 34.3%), enabling the differentiation by cluster of different cooking phases: uncooked, undercooked (described by degree of gelatinisation and rigid protons' populations [FID and T2 ]); medium‐cooked (described by higher mobility protons [T2 E1, T2 E2 and %PopE2]), cooked at suggested cooking time (described by viscoelastic properties) and over‐cooked pasta by molecular mobility parameters (T2 D, T2 E and %PopF). Nuclear magnetic resonance relaxometry was a valuable tool to describe the entire cooking process, whereas viscoelastic properties effectively characterised suggested cooking time. Abstract : Pasta was investigated during cooking at different scales of investigation. The considered parameters allowed to discriminate different cooking phases, as a function of the changes occurring at different scales of investigation.